Analysis of Personnel's Understanding of Safety Culture in the Implementation of Safety Management System at Yogyakarta International Airport - Prakoso, Hendro Agung; Tamara, Amelia Puspa (CV. Rayyan Dwi Bharata, 2023)
The global spread of industries towards the era of Industry 4.0, encompassing the integration of cyber technology and automation. Safety Management Systems (SMS) are employed at each airport differently due to their distinct characteristics. Airport security and order disruption are security issues. Cases such as apron breaches, trespassing, and negligence occur. Aviation accidents pose security issues stemming from SMS implementation, operational oversight, aircraft certification, and flight health factors. There are 8 accident categories and 22 serious incidents resulting in 5 fatalities.This research employs a qualitative approach with a descriptive method. To attain answers, the researcher designed a qualitative research design. Qualitative research aims to investigate, discover, describe, and explain the quality of social influences. Data analysis is conducted through data collection, reduction, display, and conclusion drawing. Validity is ensured using source triangulation. The research findings reveal that personnel safety culture at Yogyakarta International Airport aligns with SOP. Out of 165 criteria, the achievement rate is 92.7%, indicating a positive relationship between safety culture and safety management system (KP 622/2015). The effectiveness of safety management system implementation at the airport is 72%. Strategies like Avoidance, Reduction, and Segregation are used to mitigate risks. Although risks cannot be entirely avoided or eliminated, adherence to standard operating procedures (SOP) and risk mitigation through facilities and human resources help minimize these risks.